2018
DOI: 10.1186/s40413-018-0214-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of patient-reported outcomes in severe allergic asthma by omalizumab treatment: the real life observational PROXIMA study

Abstract: BackgroundData on the prevalence of perennial versus seasonal allergic asthma in Italy are lacking; moreover, there is limited evidence on the effect of omalizumab on patient-reported outcomes in Italian patients with severe allergic asthma. PROXIMA, an observational, multicenter study, was designed to assess the prevalence of perennial versus seasonal allergic asthma (cross-sectional phase) and the effect of omalizumab on improving illness perception, quality of life (QoL) and asthma control of Italian patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
(39 reference statements)
3
25
0
Order By: Relevance
“…The PROXIMA (Patient Reported Outcomes and Xolair ® In the Management of Asthma) study was an observational, non-controlled, multicenter, two-phase study in Italian severe allergic asthma (SAA) patients, aimed at assessing the prevalence of perennial environmental allergies (during the cross-sectional phase) and the rate of disease control after up to 12 months of omalizumab treatment (during the longitudinal phase). The secondary objectives of the study included the assessment of patients’ disease perception and level of asthma control during both the cross-sectional and longitudinal phases and patients’ compliance to and persistence with omalizumab, rate of exacerbations and patients’ QoL during the longitudinal phase [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The PROXIMA (Patient Reported Outcomes and Xolair ® In the Management of Asthma) study was an observational, non-controlled, multicenter, two-phase study in Italian severe allergic asthma (SAA) patients, aimed at assessing the prevalence of perennial environmental allergies (during the cross-sectional phase) and the rate of disease control after up to 12 months of omalizumab treatment (during the longitudinal phase). The secondary objectives of the study included the assessment of patients’ disease perception and level of asthma control during both the cross-sectional and longitudinal phases and patients’ compliance to and persistence with omalizumab, rate of exacerbations and patients’ QoL during the longitudinal phase [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Canonica et al demonstrated that the use of omalizumab in severe allergic asthma improves patient outcomes such as QoL and patients' FIGURE 4 | Total EE (estimated energy expenditure) variation at different follow-ups in the biologic therapy (BT) omalizumab group and in the BT mepolizumab group. illness perception (Canonica et al, 2018). PA levels are strictly related to QoL: PA levels are improved in populations with a high QoL (Mazzeo et al, 2016;Monda et al, 2017b;Wu et al, 2017;Cordova-Rivera et al, 2018a;Sessa et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed inclusion/exclusion criteria have been described previously. 16 The study consisted of a crosssectional phase and a 12-month longitudinal prospective phase. After screening, patients entered into the cross-sectional phase designed to estimate the pattern of allergic asthma (perennial versus seasonal).…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…15 PROXIMA, an observational, multicenter twophase study (cross-sectional and longitudinal phase) conducted in patients with SAA showed that omalizumab reduced exacerbation rates by 87% and effectively controlled asthma after 6 and 12 months of treatment, improving quality of life of these patients. 16 A high proportion of the study population (longitudinal phase) responded to the omalizumab treatment with a response rate of 89%-96%.…”
Section: Introductionmentioning
confidence: 99%